2019
DOI: 10.1111/jcmm.14485
|View full text |Cite
|
Sign up to set email alerts
|

Cordycepin ameliorates cardiac hypertrophy via activating the AMPKα pathway

Abstract: Increase of myocardial oxidative stress is closely related to the occurrence and development of cardiac hypertrophy. Cordycepin, also known as 3'‐deoxyadenosine, is a natural bioactive substance extracted from Cordyceps militaris (which is widely cultivated for commercial use in functional foods and medicine). Since cordycepin suppresses oxidative stress both in vitro and in vivo, we hypothesized that cordycepin would inhibit cardiac hypertrophy by blocking oxidative stress‐dependent rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…Five of these met the eligibility criteria (see the Methods section). The outcomes were activation of AMPK indicated by increasing phosphorylation at Thr 172 (three articles) and also inhibiting mTOR indicated by reduced the phosphorylation at Ser 2448 (two articles), confirming the effects observed in tissue culture [35,142,164,183,184]. For details see Table 2.…”
Section: Signal Transduction Effects In Animal Modelssupporting
confidence: 56%
See 3 more Smart Citations
“…Five of these met the eligibility criteria (see the Methods section). The outcomes were activation of AMPK indicated by increasing phosphorylation at Thr 172 (three articles) and also inhibiting mTOR indicated by reduced the phosphorylation at Ser 2448 (two articles), confirming the effects observed in tissue culture [35,142,164,183,184]. For details see Table 2.…”
Section: Signal Transduction Effects In Animal Modelssupporting
confidence: 56%
“…We noted 45 papers claiming that the cytotoxic effect of cordycepin at bioactive concentrations was low. We noted the highest concentration which promoted cell survival or did not cause statistically significant cell death in these papers and determined the median and the range [ 28 , 29 , 30 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 69 , 70 , 80 , 95 , 98 , 102 , 105 , 106 , 117 , 142 , 145 , 164 , 184 , 240 , 270 , 301 , 315 , 317 , 326 , 327 , 328 , 329 , 330 , 331 , 332 , 333 , 334 , 335 , 336 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous studies have found that AMPK activation appears to have a protective effect on cardiomyocytes under MI/R by decreasing apoptosis, improving post-ischemic recovery, and reducing myocardial infarction (MI) ( Wu and Zou, 2020 ). Interestingly, cordycepin has been reported as a pro-drug that activates AMPK by being converted into the AMP analog cordycepin monophosphate ( Wu et al, 2014 ; Wang et al, 2019 ; Hawley et al, 2020 ). Moreover, recent studies have demonstrated that AMPK regulates mitochondrial fusion and mitophagy to sustain mitochondrial homeostasis under stress conditions ( Toyama et al, 2016 ; Zhang et al, 2019 ), indicating the key role of AMPK in mitochondrial dynamics.…”
Section: Introductionmentioning
confidence: 99%